Betancourt Mendieta, A. (2018). América Latina: cultura letrada y escritura de la historia. Anthropos & Siglo XXI. 189 pp. - Mora Muro, Jesús Iván (Letras Históricas E-ISSN: 2448-8372, 2019)
Reseña de libro.